Indigenous fishing techniques and their effectiveness as perceived by fishers in Cachar District, Assam, India - Nath, Kapil Deb; Borah, Simanku; Chetia, Barkha Rani; Saikia, Nabadeep; Saud, Bhaskar J.; Majumdar, Ranendra Kumar (Indian Journal of Fisheries, 2018)
The present study investigated traditional fishing devices namely Bundh, Dori and Gori Jal operated by fishers of Cachar District, Assam in rivers and small canals. The study was carried out in Ghagra River and adjoining small canals. Water current as well as indigenous knowledge of fishers on movement of fishes and foraging behaviour of freshwater prawns were found to be utilised to a great extent to catch the target species. Assessment of the effectiveness and rationality as perceived by fishers and experts respectively showed that Bundh fishing was highly effective Mean Perceived Effectiveness Index (MPEI score >2.5) whereas the other two fishing techniques namely Dori and Gori Jal were effective (MPEI score >2). All the three indigenous fishing techniques were found to be rational with a mean score â‰¥3.